2019
DOI: 10.1038/s41598-019-46756-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Genetic Determinants of Isoniazid and Rifampicin Resistance in Mycobacterium tuberculosis in Southern India

Abstract: Drug-resistant tuberculosis (TB), one of the leading causes of death worldwide, arises mainly from spontaneous mutations in the genome of Mycobacterium tuberculosis . There is an urgent need to understand the mechanisms by which the mutations confer resistance in order to identify new drug targets and to design new drugs. Previous studies have reported numerous mutations that confer resistance to anti-TB drugs, but there has been little systematic analysis to understand their genetic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 76 publications
1
32
0
Order By: Relevance
“…Drug-resistant mutations in rpoB were mostly located in the 81-bp region of rpoB (rifampicin resistance determining region, RRDR). These rpoB mutations often come with fitness costs [20]. In this study, we reported the fitness cost of 14 types of rpoB base substitution and one type of 12-bp insertion.…”
Section: Discussionmentioning
confidence: 95%
“…Drug-resistant mutations in rpoB were mostly located in the 81-bp region of rpoB (rifampicin resistance determining region, RRDR). These rpoB mutations often come with fitness costs [20]. In this study, we reported the fitness cost of 14 types of rpoB base substitution and one type of 12-bp insertion.…”
Section: Discussionmentioning
confidence: 95%
“…A previous report found a high prevalence of the katG S315T gene mutation among HR-TB/MDR-TB/XDR-TB strains (58.7%-68.6%) in Thailand. 16,17 The prevalence of katG S315T varied according to the geographic region: Southeast Asia (78.4%), 18 Vietnam (85.3%), 19 Myanmar (61.2%), 20 Taiwan (29.3%), 6 Japan (25%), 10 India (67.6%), 21 Sri Lanka (67.8%), 22 Romania (52.8%), 23 Cameroon (64%), 24 and the United States (38%). 8 The different ranges of MIC found for each mutation gene can be explained by gene variation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the KatG and InhA are responsible for the mechanism of resistance to INH. We have mapped the resistance mutations in KatG and InhA onto their protein structures and predicted the effects on protein stability, protein-protein interactions and protein-drug interactions using SDM and mCSM (Munir et al, 2019).…”
Section: Tuberculosismentioning
confidence: 99%
“…These mutations were also found to alter the interactions either with the drug or the surrounding residues, and were predicted by mCSM-lig to decrease the affinity of the drug toward the protein. We also analyzed the impact of four mutations (L516P, N416T, V483G, and I491T) on RpoC, which are located at the interfaces with other subunits in RNA polymerase complex (Munir et al, 2019). These mutations were predicted to have a destabilizing impact on protein stability and protein-protein interactions.…”
Section: Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation